Emergence of cHz Quasiperiodic Oscillations from a Low-angular-momentum Flow onto a Supermassive Black Hole - Indu K. Dihingia; Yosuke Mizuno (The Astrophysical Journal Letters)
Quasiperiodic oscillations (QPOs) are very common in black hole accretion systems that are seen from the modulations in luminosity. Many supermassive black hole sources (e.g., RE J1034+396, 1H 0707-495, MCG-6-30-15, 1ES 1927+654, Sgr A*) have been observed to exhibit QPO-like variability in the range of mHz in different energy bands (e.g., radio, near-IR, X-rays). Due to the shorter infalling time, low-angular-momentum accretion flows can have resonance close to the black hole, which will raise variability cHz or beyond QPOs for supermassive black holes. In this study, for the first time, we show that such resonance conditions can be achieved in simulations of low-angular-momentum accretion flows onto a black hole. The QPOs could have values beyond ν _QPO ≳ 0.1–1 × 10 ^7 M _⊙ / M _BH cHz and the harmonics have a ratio of 2:1. Hunting these cHz QPOs down will provide a smoking gun signature for the presence of low-angular-momentum accretion flows around black holes (e.g., Sgr A*, 1ES 1927+654).